PENGARUH KEPEMIMPINAN DAN INSENTIF TERHADAP MOTIVASI KERJA PEGAWAI NEGERI SIPIL DI DINAS PENDIDIKAN DAERAH PROVINSI SULAWESI UTARA - Y. Tahir, Yoyon; R. Dilapanga, Abdul; S. R. Siwij, Devie (Gapenas Publisher, 2024)
This study aims to determine the influence of leadership and incentives on work motivation among civil servants (PNS) at the Regional Education Office of North Sulawesi Province. This research adopts a quantitative approach, utilizing primary data collected through questionnaires distributed to employees of the Regional Education Office. The results show that, partially, leadership significantly affects work motivation among civil servants. Similarly, incentives also have a significant influence on work motivation. Simultaneously, leadership and incentives significantly contribute to improving work motivation. This study concludes that leadership and incentives are essential factors in enhancing work motivation among civil servants at the Regional Education Office of North Sulawesi Province.